Serological Monitoring as an Indicator of Population Immunity against Hepatitis B in the Population of the Russian Federation - D. V. Solov’yov; M. I. Korabel’nikova; E. N. Kudryavtceva; N. V. Vlasenko; Y. V. Panasyuk; Z. S. Rodionova; V. V. Klushkina; D. V. Dubodelov; V. M. Glinenko; T. A. Semenenko; S. N. Kuzin; V. G. Akimkin (Эпидемиология и вакцинопрофилактика)
Hepatitis B (HB) remains one of the serious medical and social health problems, and to assess the epidemiological situation, it is necessary to analyze the state of population immunity by collecting information on its intensity during serological studies. The aim of the work is to assess the level of population immunity against HB in the population of the Russian Federation in 2017 to 2022. Materials and methods. The results of serological monitoring for the presence of anti-HBs, provided by territorial laboratories of medical institutions of each subject of the Russian Federation in 2017 to 2022, were analyzed. The cohort of subjects in each subject of the Russian Federation consisted of persons in the age groups 3–4, 16–17, 20–29, 30–39, 40–49 years old, numbering at least 100 people each. The analysis of the obtained data for 6 years (2017–2022) was carried out using averaged data for every two years – 2017–2018, 2019–2020 and 2021–2022. The number of study cohorts during these time intervals was 88,151, 84,166 and 97,274 people, respectively. Results and discussion. The average values of the proportion of persons with immunity against HB were 69.0% in 2017–2018, 66.2% in 2019-2020 and 61.3% in 2021–2022. The highest proportion of people with protective immunity against hepatitis B was observed in the age group of 20-29 years. The proportion of children 3-4 years old who had anti-HBs detected at a concentration exceeding 10 IU/l was 65.8–72.5%, and 16–17 years old – 49.6–64.9%. The intensity of post-vaccination immunity against HB in children 16-17 years old should be considered insufficient. Conclusion. An analysis of serological studies results for the period from 2017 to 2022 showed that the potential of vaccine prevention of hepatitis B, carried out since 2006 within the framework of the priority National Project «Health», is not fully realized.